2014
DOI: 10.11118/actaun201159070237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impacts of Common Agricultural Policy on plant production in the Czech Republic

Abstract: Common agricultural policy has fundamentally projected itself into the business management of individual agricultural businesses. The submission addresses the assessment of the effects of subsidy policy on the production, costs and profit of agricultural businesses that engage predominantly in plant production. At the same time, it determines the effects of subsidy policy on demand for the production factors of labour and land. To the research questions more than 100 agriculture businesses were analyzed. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…Pechrová and Vlašicová (2013) came to the same conclusion in the case of organic farms. On the other hand, Malá et al (2011) concluded that in the plant production, the direct payments do not motivate doi: 10.17221/110/2014 -AGRICECON agricultural businesses to increase the production. Hence, it seems that the effect depends on the type of production of the agricultural holding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pechrová and Vlašicová (2013) came to the same conclusion in the case of organic farms. On the other hand, Malá et al (2011) concluded that in the plant production, the direct payments do not motivate doi: 10.17221/110/2014 -AGRICECON agricultural businesses to increase the production. Hence, it seems that the effect depends on the type of production of the agricultural holding.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Malá et al (2011) found a positive effect of direct payments on the increasing of the profit of agricultural producers. Boudný et al (2011) found out that the higher are the SAPS and the Top-Up subsidies, the higher is the efficiency of farms in the CR.…”
Section: Doi: 1017221/110/2014 -Agriceconmentioning
confidence: 99%
“…This assumption is likely to be very restrictive regarding public subsidies, since it is theoretically demonstrated that public subsidies may influence the inputoutput space (see Hennessy, 1998;Serra et al, 2006;Ciaian and Swinnen, 2009). Second, likely to account for this theoretical fact, a number of papers, using SFA or DEA, model subsidies as input or as output (see Silva et al, 2004;Hadley, 2006;Kroupová and Malý, 2010;Malá et al, 2011;Trnková et al, 2012;Rasmussen, 2010;Silva and Marote, 2013;Mamardashvili et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such goal is fulfi lled by a whole spectrum of instruments, from direct payments within the fi rst pillar of CAP, to various agroenvironmental subsidies within the second pillar. Such instruments, besides aff ecting the total income of households or the profi t of companies, also aff ect the level of agricultural production and costs, prices, as well as farm structure (Henningsen et al, 2011;Malá et al, 2011). Witzke and Noleppa (2006) emphasize that two basic variables, which measure the eff ectiveness of public policy, is the rate of allocation and redistribution eff ects.…”
mentioning
confidence: 99%